The effect of different periods of aestivation on recovery and nutritional composition of Apple snail (Pomacea sp.) - S. Srijad; Vasan Sang-in; K. Pilapang; R. Yomla (International Journal of Agricultural Technology, 2025)
The results showed a 100% recovery of all experimental groups. The survival rate of aestivation groups (2 weeks, 4 weeks, and 8 weeks) showed a significant difference, and the survival rate was 94.78±4.50, 90.82±3.11, and 88.78±2.86 percent, respectively. The average weight at the end of the experiment was 19.3±1.2, 15.1±3.7, 15.4±3. 6 and 13.8±2.9 g, respectively, which were not significantly different (P>0.05). The nutritional composition after aestivation showed a significant difference (P<0.05) in protein values among the groups. The protein value was 47.53±0.44, 51.17±0.53, 52.88±0.18, and 53.95±0.24 percent, respectively. The protein values showed an increasing trend over the aestivation period, while the fat was between 2.1-2.4 percent, and fiber was between 0.3-0.4 percent were not significantly different (P>0.05). The percentage of ash was significantly different (P<0.05), with values ranging from 17.0 to 19.4. It was shown that higher ash percentages were observed in the 4-week and 8-week groups. The percentages of NFE with values ranging from 24.1 to 33.1. Meanwhile, NFE percentages were higher in the control group and showed a decreasing trend over the study period. The percentage of calcium was significantly different (P>0.05), with values ranging from 5.6-6.7, while the percentage of phosphorus was about 0.6 percent, which was not statistically different (P>0.05). The survival rate trend of apple snails decreased with increasing aestivation period. Similarly, the body weight and NFE values decreased, but the body protein level increased.
Keywords: Mollusks and Parasites Studies; Medical and Biological Ozone Research; Therapeutic Uses of Natural Elements